Analysis of the Success of the PLN Mobile Application Using the DeLone and McLean - Ni Putu Viky Aryani; ⁠I Made Candiasa; I Made Gede Sunarya (P3M Politeknik Negeri Bengkalis, 2025)
The advancement of digital technology has driven a transformation in public services, including the electricity sector. PT PLN (Persero) responded to this change by launching the PLN Mobile application; however, a gap between user expectations and actual experiences remains evident. This study aims to evaluate the success of the PLN Mobile application using the DeLone and McLean (D&M) model, focusing on five dimensions, system quality, information quality, user interest, user satisfaction, and net benefits. A quantitative method was employed through Structural Equation Modeling (SEM) with AMOS based on data from 150 active respondents. The goodness-of-fit results confirmed that the model was acceptable (RMSEA = 0.039; CFI = 0.977; TLI = 0.975). Path analysis revealed that system quality (β = 0.240; p = 0.006) and information quality (β = 0.381; p < 0.001) positively influence user interest. User interest enhances satisfaction (β = 0.501; p < 0.001), while satisfaction significantly affects net benefits (β = 0.420; p < 0.001). In contrast, the direct effects of system and information quality on satisfaction and the direct effect of user interest on net benefits were not significant. The novelty of this study lies in validating the D&M model within the context of a public utility application in Indonesia, emphasizing the mediating role of user satisfaction. These findings highlight that improving system and information quality not only stimulates user interest but also ensures satisfaction as the key mediator driving the realization of net benefits from the PLN Mobile application.